English Teacher’s Attitudes and Practices of ICT Adoption in English Language Classrooms - Syauqiyah Awaliyah Alfiani Nur; Muliati Muliati; Munir Munir (Har Press Indonesia, 2021)
This study aims to investigate English teachers’ attitudes and practices of ICT adoption in English language classroom. The participants of this study were 20 teachers of English in the senior secondary school level of Makassar. Drawing on semi-structured interview data, I found that the teachers’ attitudes of ICT adoption in English language classroom were positive. The attitudes are proven on the teachers’ results interview which says there is some easiness in integrating ICT in classroom. This study also showed that the English teachers’ practices in ICT-based learning were not yet optimally implemented. There was a gap between their attitudes and practices in ICT adoption in English Language Classroom. To make them equal, the teachers need more training to improve their skills in using ICT tools for English teaching purpose as well as the sufficient of ICT tools which provided by school. The result of the practices of ICT adoption in English language classroom by English teachers was in applying stage if consulted with the continuum of ICT development.